EP-630 Pheochromocytoma Associated with SDHB Mutation: A case report. (9th August 2022) - Rezkallah, Emad; Elsaify, Wael
Abstract: Introduction: Pheochromocytomas and paragangliomas are rare neuroendocrine tumors arising from the chromaffin cells of the adrenal medulla or extra-adrenal tissues. 10% to 20% of tumors are detected before age 18 years. Approximately 10%–15% of pheochromocytoma and 20%–50% of paraganglioma are malignant. Up to 24% of the cases are familial where they may be associated with genetic syndromes like MEN 2, succinate dehydrogenase subunit B (SDHB) gene mutations and VHL syndrome. Germline mutations in SDHB gene increase the risk of PGLs/ PHEOs and RCC with 38%-83% risk of malignancy. We represent a rare case of pheochromocytoma associated with SDHB mutation in a child. Case presentation: A 17-year old patient presented with repeated vomiting and hypertension. BMI was 14.4 kg/m2, BP was 140/112 mmgh, PR was127 peats/min. The rest of the clinical examination was unremarkable. Plasma and 24-hour urinary metanephrines levels were highly elevated together with Chromogranin A level. Abdominal CT and MRI scans revealed an enlarged right adrenal gland measuring approximately 45 mm, indenting but not invading the posterior aspect of the IVC. Management: Treatment was initiated with α-blockers; (Doxazosin then phenoxybenzamine); followed by β-blockers. The patient underwent laparoscopic right adrenalectomy. The tumor was 50×30×30 mm and weighting 58g. The tumor was positive with chromogranin, and S100. The PASS score was 2. Genetic mutation was detected at SDGB (c.72+1G>A). Conclusion: We recommend genetic testing for all suspecting cases of PHEO/PGLs to establish the appropriate follow-up plan.